Psikologi Jawa Surya Mentaraman dan Trauma Perempuan: Sebuah Pendekatan Tokoh Firdaus dalam 'Perempuan di Titik Nol - Sunarno; Suhartono; Haris Supratno; Heny Subandiyah (Singular: Journal of Pedagogical Language, Literature, and Cultural Studies, 2024)
This article examines women's trauma in the novel Perempuan di Titik Zero by Nawal El Saadawi using the Javanese psychological approach Mentaraman. A qualitative and descriptive approach was used to explore the traumatic experience of the main character, Firdaus, and analyze how she tried to face and overcome the suffering she experienced. Mentaraman's Javanese psychology, which emphasizes inner balance, mental peace, and psychological recovery, is the basis for understanding how Firdaus interacts with trauma and the search for identity in the context of Javanese tradition and culture. Through a literature review, this article discusses how Javanese psychology can provide a new perspective in understanding Firdaus' mental and emotional response to the oppression, violence and helplessness he experienced. The results of the analysis show that even though Firdaus is trapped in a state of deep trauma, Javanese psychological values ​​that focus on self-recovery and inner harmony can explain Firdaus' efforts to achieve peace in facing her past. This article provides insight into how women's trauma can be understood through the lens of Javanese psychology and the importance of mental balance in the recovery process.